Active Learning Improves Financial Education: Experimental Evidence from Uganda - Tim Kaiser; Lukas Menkhoff (Center for Economic Studies and ifo Institute (CESifo), 2022)
We conduct a randomized field experiment to study the effects of two financial education interventions offered to small-scale retailers in rural western Uganda. The treatments contrast “active learning” with traditional “lecturing” within standardized lesson-plans. After six months, active learning has a positive effect on savings and investment outcomes, in contrast to small or zero effects for lecturing. After four years, estimates come with substantial uncertainty but are generally larger for the active learning group, such as a 60 percent increase in investments. As an adverse outcome, reported late payment on loans increases by about 30 percent for both treatments. The findings suggest that teaching methods can play an important role in affecting how financial education programs impact financial behavior and outcomes.
Keywords: O16; I21; G53; 330; financial behaviour; financial literacy; active learning; lecturing; training method; field experiment